Influence of upscaling accumulative roll bonding on the homogeneity and mechanical properties of AA1050A - Ruppert, Mathis; Böhm, Wolfgang; Nguyen, H.; Höppel, Heinz Werner; Merklein, Marion; Göken, Mathias (Journal of Materials Science, 2013)
Accumulative roll bonding (ARB), as a method for production of ultrafine grained materials, is frequently supposed to be easily transferable to established industrial production lines. In literature, however, common sheet dimensions used for ARB in a laboratory scale are between 20 and 100 mm in width. In order to quantify the potential of upscaling the ARB process to a technological relevant level, sheets of AA1050A with an initial sheet width of 100–450 mm were accumulative roll bonded up to 8 cycles. In this regard, three different rolling mills of distinct dimensions were used for processing of the sheet material. The influence of process parameters and the reproducibility of the process, in terms of mechanical properties and homogeneity of the sheets, were studied by means of mechanical and microstructural characterization. Both appear to be largely independent on the sheet size and the rolling mill utilized for production. Only small deviations after the first cycles could be detected, vanishing in subsequent cycles due to the features of microstructural evolution. The finally obtained results indicate a high potential for industrial application of ARB and illustrate the possibility to upscale the process to a level necessary for that purpose.
WW1::970